2013
DOI: 10.1177/1741143213499254
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing principals’ retirement decisions

Abstract: This study, conducted in one state in the United States, replicated similar research from over a decade ago to compare principal demographics and reasons for remaining or leaving the profession. Demographics have trended with the nation. Principals are older, more diverse and are largely eligible for retirement within the next five years. Similar demographics are noted in Australia, New Zealand and the United Kingdom. The reasons for retiring have changed dramatically since the first survey. External mandates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…In addition, higher stress is associated with higher attrition rates of principals and superintendents (Kelley and Peterson, 2006; Winter et al, 2007). In academic year 2012–2013, principals’ most common reasons for leaving were: external mandates from national or state sources; need for more time with family; time requirements of the position; frustration with barriers; internal mandates; and burnout (Reames, Kochan, and Zhu, 2013). These reasons contrast sharply with those provided in 1999, when the top reason for leaving was to get another position (Reames et al, 2013), providing evidence that in the early-21st century, there has been a strong increase in pressure on principals and thus, the reasons for leaving a job have become more complex.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, higher stress is associated with higher attrition rates of principals and superintendents (Kelley and Peterson, 2006; Winter et al, 2007). In academic year 2012–2013, principals’ most common reasons for leaving were: external mandates from national or state sources; need for more time with family; time requirements of the position; frustration with barriers; internal mandates; and burnout (Reames, Kochan, and Zhu, 2013). These reasons contrast sharply with those provided in 1999, when the top reason for leaving was to get another position (Reames et al, 2013), providing evidence that in the early-21st century, there has been a strong increase in pressure on principals and thus, the reasons for leaving a job have become more complex.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In academic year 2012–2013, principals’ most common reasons for leaving were: external mandates from national or state sources; need for more time with family; time requirements of the position; frustration with barriers; internal mandates; and burnout (Reames, Kochan, and Zhu, 2013). These reasons contrast sharply with those provided in 1999, when the top reason for leaving was to get another position (Reames et al, 2013), providing evidence that in the early-21st century, there has been a strong increase in pressure on principals and thus, the reasons for leaving a job have become more complex. In surveys, 91% of principals identified burden of the job as reason for leaving, with district and state mandates frequently cited as a major source of stress (Owings, Kaplan, and Chappell, 2011; Pijanowski, Hewitt and Brady, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, previous studies have pointed out that principals leave the profession for many reasons: taking a position elsewhere in the state, conflict with the local community, or frustration (Kochan and Spencer, 1999); avoiding the feeling of stagnation (Fidler et al, 2009); a high volume of working hours, with an average of 59 hours per week (Lavigne et al, 2016); difficulty in accepting new challenges arising from previously routine tasks, lack of support, and family reasons (Sheppard, 2010). In contrast, Reames et al (2014) reported that, based on their findings, some principals remained at the same school because they believed that they still felt a crucial duty to empower their teachers and students’ capabilities, received strong backing from the community and from their colleagues, and enjoyed the post and role of a school principal. However, they also believed principals would leave the post for family and health problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, because the measure used is driven by the research question(s) posed, it is important to note that even within one type of measurement, such as dichotomous measures, there are differences. For instance, dichotomous measures include all the following scenarios: whether a principal intends to leave his or her school (e.g., Reames et al, 2014; Tekleselassie & Villarreal, 2010), whether a principal actually leaves his or her school (e.g., Li, 2015; Papa, 2007), or whether a principal leaves after his or her first year or after the second year (Burkhauser et al, 2012). These differences matter both for how we understand and theorize about principal turnover and for how policy makers should think about and try to address turnover.…”
Section: Defining and Measuring Principal Turnovermentioning
confidence: 99%